Assessing the Impact of Climate Change on Global Crop Yields and Farming Practices - , Anand Naik; , Mahantesh Jogi; , Shreenivas B V (Archives of Current Research International, 2024)
Climate change is recognized as one of the most pressing challenges of our time, with profound implications for global food security. This review article delves into the multifaceted impacts of climate change on crop yields and farming practices on a global scale. By synthesizing recent research findings, identifying key challenges and opportunities, and exploring adaptation strategies, this review provides a comprehensive analysis of the complex interplay between climate change and agriculture. The effects of climate change on agriculture are diverse and far reaching. Alterations in weather patterns, including shifts in temperature, precipitation, and frequency of extreme events, pose significant challenges to agricultural productivity and food security. These changes disrupt traditional farming practices, exacerbate water stress, soil erosion, and crop loss, and threaten the livelihoods of millions of farmers worldwide. Additionally, changes in pest and disease dynamics have further compounded the challenges faced by agricultural systems under pressure from climate variability. These challenges, there are opportunities for innovation and adaptation in the agricultural systems. This review highlights the potential of climate-smart agricultural practices such as crop diversification, conservation agriculture, and precision farming to enhance resilience and mitigate the impacts of climate change on crop yields. investments in climate-resilient crop varieties, improved water management techniques, and sustainable land management practices offer pathways for building adaptive capacities and ensuring food security in a changing climate. addressing the complex challenges of climate change adaptation in agriculture requires concerted action at multiple levels. This review emphasizes the importance of coordinated efforts among policymakers, researchers, farmers, and other stakeholders in developing and implementing effective adaptation strategies. Such strategies should be context-specific, socially equitable, and environmentally sustainable, considering the diverse needs and priorities of different regions and communities. This review underscores the urgent need for coordinated action to build resilient and sustainable food systems in the face of a changing climate. By synthesizing the latest research findings, identifying key challenges and opportunities, and exploring adaptation strategies, this review aims to inform policymakers, researchers, and practitioners about the imperative of addressing climate change’s impacts on agriculture. Only through collaborative and transformative action can we ensure food security for the present and future generations in a rapidly changing world.